Polycythemia in primary care: diagnostic evaluation and management - Morales-Ceballos, Lizeth X. (2025)
Objective: To develop a narrative synthesis on polycythemia, a prevalent condition that poses diagnostic challenges in primary health care. Materials and methods: A non-systematic literature review was conducted using six databases (PubMed, SCOPUS, ScienceDirect, SciELO, Redalyc, and Google Scholar), covering publications from January 2005 to December 2024. Result: Polycythemia is an underdiagnosed blood hyperviscosity condition with high prevalence and a strong association with cardiovascular events, particularly in cases of polycythemia vera and chronic obstructive pulmonary disease. Conclusion: This review provides a practical approach for early etiological diagnosis and timely treatment of polycythemia. The proposed algorithm optimizes resource use in primary care and may reduce diagnostic delays, improving clinical decision-making.